(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To compare the frequency of complications of Paediatric femoral shaft fractures treated with hip spicca versus flexible nails. Methods: This retrospective cross sectional study was conducted in Orthopedics and Traumatology division of Lady Reading Hospital Peshawar. The medical records of all children with femoral shaft fractures fulfilling the inclusion criteria and who were treated with hip spicca or titanium flexible nails in time period extending from 24th July 2019 to 23rd January 2022 were reviewed. Patients were divided into Spicca group(S) and Flexible nail group(F). Complications in both groups were documented and compared. Results: The record of 480 children was reviewed. The spicca group(S) and Flexible nails group(F) had 240 children each. The mean age of S group was 5.32±2.2 years and F group was 7.77±1.6 years. Both the S group and F group had 180(75%) and 141(58.75%) male children respectively. Right femoral fractures were present in 132(55% ) children in S group and 141(58.75%) in F group. Union was achieved in both groups. The average union time was 6.2±3.2 weeks in S group and 5.32±1 weeks in F group. Overall 64(26.66%)children in the S group and 42(17.5%) children in the F group had complications. The frequency of knee stiffness, malunion and shortening was significantly more in S group than in F group. (p<0.05) Conclusion: Paediatric femoral shaft fractures treated with hip spicca casting had higher complications than flexible nails.